Conceptualizing Service-Related Trauma: Controversies, Challenges, and Opportunities in the Canadian Context - Beks, Tiffany A.; Cairns, Sharon L.; Kassan, Anusha; Schwartz, Kelly D. (Canadian Journal of Counselling and Psychotherapy, 2021)
This article considers three perspectives that have figured prominently in the conceptualization of psychological trauma related to military service in the Canadian context—that of military institutions, that of military members, and that of counselling psychologists. A closer examination of these views reveals points of contention regarding the origins, terminology, and cultural relevance of conceptualizations of service-related trauma, such as post-traumatic stress disorder By drawing from theoretical, empirical, critical, and anecdotal literature, this article highlights the need for counselling psychologists to continually evolve their understanding of the broader contexts in which service-related trauma occurs and to honour military members’ knowledge of diverse sources of traumatic suffering.